A Review of Assessment Methods for Postural Control and Balance in Intellectual Disabilities - Esmail Balayi; Parisa Sedaghati; Hamed Zarei (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims: Balance is one of the important factors that help to maintain the independent life of people with intellectual disabilities. A variety of methods are used to assess balance in these individuals. However, so far no review study has been conducted to determine what kind of tests are used to assess balance in this group. Therefore, The purpose of this study was to investigate the methods of assessing postural control and balance used in studies on intellectual disabilities.Methods: In this study, a comprehensive search was performed on functional assessment tests of balance in people with intellectual disabilities. PubMed, Medline, Web of Science, ScienceDirect, Cochrane Central Register of Controlled Clinical Trials, Google Scholar, Scopus, Magiran, IranDoc, Iran Medex, MedLib, and SID were searched from 1991 to November 2020. After collecting the search results, first, the title and then the summary of the articles were studied. If the articles met the inclusion criteria, the results were used in the review study and otherwise discarded.Results: Based on the criteria and objectives of the research, 20 articles were selected after the evaluation process. All articles were provided in full text. Then, 23 Functional Balance Assessment Tests were used to measure functional balance in people with intellectual disabilities.Conclusion: Studies had examined the evaluation of functional balance in intellectual disabilities in several ways; therefore, it seems that a specific test cannot be suggested to measure the balance of intellectually disabled people.